O Direito do trabalho como instrumento de inclusão social das minorias e de grupos vulneráveis - Ferreira, Marília Lustosa (2020)
The present research aims to analyze whether Labour Law is a democratic instrument for social inclusion of minorities and vulnerable groups composed of women, blacks, LGBTI and people with disabilities in view of the inequalities found for these people to be inserted accepted and remain in the work environment that recognizes and respects their inherent characteristics above all their human dignity. It also aims to demonstrate that among the Fundamental Human Rights inherent to all human beings human dignity is a precursor to achieving the effective social inclusion of these people who are in a condition of vulnerability given the effectiveness of constitutional principles applicable to Labour Law. The research brings the concept of minorities and vulnerable groups as well as national and international legislation in force as mechanisms to protect against inequality of opportunity and treatment, especially in the workplace as a form of social inclusion of these people. However, in order to have equal opportunities for minorities and vulnerable groups in the workplace it is essential that the fundamental rights of these people be respected and that public policies are proposed and ensured as mechanism of social inclusion of these people. In addition another effective instrument for protecting minorities and vulnerable groups is the use of collective actions to defend their interests and rights.